Re-conceptualizing implementation outcomes of health innovations as modes or attributes: an integrated framework - Balayah, Zuhur; Stavropoulou, Charitini; Scarbrough, Harry; Nigam, Amit; Ziemann, Alexandra (Frontiers in Health Services, 2025)
The implementation of innovations in practice is challenging and often produces disappointing outcomes. Although the reasons for this are multifaceted, part of the challenge derives from the lack of consensus on how such implementation outcomes should be conceptualized and measured. In this review, we used a meta-ethnographic approach to enhance our theoretical conceptualization of implementation outcomes. By situating such outcomes within the overall process of implementation, we were able to unpack them analytically as the product of two major components, which we term “modes” and “attributes,” respectively. Modes comprise engagement, active implementation, and integration to foreground focal implementation outcomes. The attributes associated with the modes comprise implementation depth, implementation breadth, implementation pace, implementation adaptation, and de-implementation to indicate the features of the modes of implementation outcomes. Taken together, our analysis based on modes and attributes provides an integrated framework of implementation outcomes. The proposed framework enhances our understanding of the way in which implementation outcomes have been conceptualized in previous literature, enabling us to clarify the relations and distinctions between them in terms of translatability and complementarity. The proposed framework thus extends the conceptualization of implementation outcomes to better align with the complex reality of implementation practice, offering useful insights to researchers, practitioners, and policymakers.